Genetic and epigenetic alterations affecting expression in cervical neoplasm among North Indian patients - Afreen Naseem; Zafar Iqbal Bhat; Ponnusamy Kalaiarasan; Bhupender Kumar; Gauri Gandhi; M. Moshahid Alam Rizvi (Tumor Biology)
The recent investigation on PARK-2 , a putative tumor suppressor gene, has found that it has been altered in multiple human malignancies. However, the clinical impact of PARK-2 alteration in uterine cervix carcinoma has not yet been studied. Therefore, we aimed to examine mutations, promoter hypermethylation, and protein expression of PARK-2 among the North Indian patients and their association with clinical parameters to evaluate the implication of PARK-2 in the genesis of cervical cancer. A total of 168 patient samples were processed for mutational analysis by single-strand conformation polymorphism, sequencing, and further in silico analysis of the identified mutations. Promoter hypermethylation by methylation-specific polymerase chain reaction and expression of PARK-2 were performed using immunohistochemistry. Statistical correlation between molecular findings and the clinicopathological parameters was taken to figure out the meaningful outcome. As per our findings, 3.5% (6/168) tumors showed novel missense mutations in exon 11 of PARK-2 . In silico analysis showed high structural deviations manifested by mutations, A398D and Y391N, in both mutant proteins as compared to wild type. Promoter hypermethylation was observed in total of 29% of (48/168) tumor samples. Furthermore, 46.43% tumors (78/168) exhibited loss of PARK-2 expression in cervical carcinoma. The loss of expression of PARK-2 when correlated with clinical parameters resulted in significant association with tumor stage (p = 0.002) and with histological grade (p = 0.025). However, only clinical stage remained significant after Bonferroni correction (p < 0.007). A trend was observed between PARK-2 promoter hypermethylation and its protein expression. Our study provided sufficient information and insight for investigation of PARK-2 and highlighted its role as a tumor suppressor gene in cervical cancer in North Indian population.